Studi Literatur: Pengalaman Menyusui pada Ibu Usia Remaja - Arista Kusuma Wardani; Yanti Yanti; Irwan Taufiqur Rachman (Politeknik Kesehatan Kemenkes Mamuju, 2022)
Breastfeeding in one of the best ways to reduce infant mortality. However, UNICEF data in 2019 recorded that only 43% of newborns started breastfeeding in the first hour and 41% received exclusively breastfed. The causes of initiation and continuation of breastfeeding are closely related to the age of the mother. Adolescent mothers were found to not continue exclusive breastfeeding. This article aims to explore the experience of exclusive breastfeeding for adolescent mothers. The method used is a literature study. Research questions were identified using the PEOS (Population, Exposure, Outcome, Study Design) framework. The journals used in the literature review were obtained through the Pubmed, Science Direct and Google Scholar databases from 2010-2020. The keywords used according to MESH (Medical Subject Heading) are